2020
DOI: 10.3390/s20030801
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Data-Security Ontology for IoT

Abstract: Although current estimates depict steady growth in Internet of Things (IoT), many works portray an as yet immature technology in terms of security. Attacks using low performance devices, the application of new technologies and data analysis to infer private data, lack of development in some aspects of security offer a wide field for improvement. The advent of Semantic Technologies for IoT offers a new set of possibilities and challenges, like data markets, aggregators, processors and search engines, which rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Using an ontological approach they recommended suitable security services that must be adopted to address specific threats [23].Gonzalez-Gil et al presented the data security ontology for IoT (DS4IoT) by following ontological evaluative processing using novel semantic concepts. The presented work is justified by mapping the DS4IoT ontology to the NGSI-LD data model [24].The security ontology presented in their paper may act as reference ontology for naï ve researchers with predefined semantic terms. However, description of context-aware rules is not described in clear manner.…”
Section: Related Workmentioning
confidence: 99%
“…Using an ontological approach they recommended suitable security services that must be adopted to address specific threats [23].Gonzalez-Gil et al presented the data security ontology for IoT (DS4IoT) by following ontological evaluative processing using novel semantic concepts. The presented work is justified by mapping the DS4IoT ontology to the NGSI-LD data model [24].The security ontology presented in their paper may act as reference ontology for naï ve researchers with predefined semantic terms. However, description of context-aware rules is not described in clear manner.…”
Section: Related Workmentioning
confidence: 99%
“…Pedro Gonzalez-Gil et al [25] suggested the DS4IoT for IoT based on lightweight data-security ontology. Current method estimates show steady IoT development, with many works depicting an even nascent security technology.…”
Section: Literature Review Based On Data Securitymentioning
confidence: 99%
“…Assuming that an information source continuously emits a series of uncertain source symbols, if these source symbols C have a value C 1 , C 2 , ⋯, C n , the corresponding uncertainty probability is P 1 , P 2 , ⋯, P n , and these source symbols are independent of each other [11,12]. Then, the information entropy of these information source symbols can be defined as follows:…”
Section: Corporate Financing Constraints and Labormentioning
confidence: 99%